Student Narratives of Significant Learning Experiences that FosterCommitment and Agency - Rigo, Daiana (2025)
This article explores how engagement and agency emerge in higher education students through meaningful learning experiences. The study aims to understand, from students’ perspectives, which formative moments fostered these practices throughout their educational trajectories. Methodologically, it is a qualitative study based on narratives collected from 65 students attending higher education institutions in southern Córdoba, Argentina. The results are organized into three key categories: (1) situated and progressive moments of agency and engagement; (2) transformation of the learning environment through teacher and student action; and (3) perceived opportunities for action (affordances). The main findings suggest that engagement and agency are not fixed individual traits, but rather situated practices that arise within educational contexts offering meaningful pedagogical relationships, authentic tasks, and real opportunities for participation. The perception of pedagogical affordances—understood as significant opportunities for action—is crucial for activating genuine student engagement and agency. The study underscores the importance of embracing the educational risk and calls for a transformation of teaching practices towards more dialogic, flexible, and contextually responsive approaches.